Assessing inhibitors of mutant isocitrate dehydrogenase using a suite of pre-clinical discovery assays. Issue 1 (December 2017) - Urban, Daniel; Martinez, Natalia; Davis, Mindy; Brimacombe, Kyle; Cheff, Dorian; Lee, Tobie; Henderson, Mark; Titus, Steven; Pragani, Rajan; Rohde, Jason; Liu, Li; Fang, Yuhong; et al.
Abstract Isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) are key metabolic enzymes that are mutated in a variety of cancers to confer a gain-of-function activity resulting in the accumulation of an oncometabolite, D-2-hydroxyglutarate (2-HG). Accumulation of 2-HG can result in epigenetic dysregulation and a block in cellular differentiation, suggesting these mutations play a role in neoplasia. Based on its potential as a cancer target, a number of small molecule inhibitors have been developed to specifically inhibit mutant forms of IDH (mIDH1 and mIDH2). We present a comprehensive suite ofin vitro preclinical drug development assays that can be used as a tool-box to identify lead compounds for mIDH drug discovery programs, as well as what we believe is the most comprehensive publically available dataset on the top mIDH inhibitors. This involved biochemical, cell-based, and tier-one ADME techniques.